The Efficacy of Er:YAG Laser on Intrapulpal Temperature Rise of Class V Cavity Preparation - Al-Qaradaghi, Tamara S.; Mahmood, Ali S.; Dayem, Raad N. (Iraqi Journal of Laser, 2011)
The objective of this study is to determine the efficacy of class V Er:YAG laser (2940 nm) cavity preparation and conventional bur cavity preparation regarding Intrapulpal temperature rise during cavity preparation in extracted human premolar teeth. Twenty non carious premolar teeth extracted for orthodontic purposes were used and class V cavity preparation was applied both buccal and lingual sides for each tooth .Samples were equally grouped into two major groups according to cavity depth (1mm and 2mm). Each major group was further subdivided into two subgroupsof ten teeth for each (twenty cavities for each subgroup). TwinlightEr:YAG laser (2940 nm) with 500mJ pulse energy, P.R.R of 10 Hz and 63.69 J/cm2 energy density was used. The analysis of the data collected revealed that there was highly significant difference between subgroups of each group, i.e., (Er:YAG laser and conventional bur cavity preparation). Also there was a highly significant difference between both group1 and group 2 subgroups (with 1mm and 2mm cavity depth). Best results were obtained from subgroup A which represents class V cavities prepared using Er:YAG laser with energy density of 63.69 J/cm2 .Er:YAG laser cavity preparation with energy density of 63.69 J/cm2 was less temperature rise than conventional bur cavity preparation taking into account the invitro temperature rise of class V cavity preparation.